Binocular visual experience drives the maturation of response variability and reliability in the visual cortex - Xiangwen Hao; Qiong Liu; Jiangping Chan; Na Li; Xuefeng Shi; Yu Gu (iScience, 2022)
Summary: A fundamental challenge of neuroscience is to understand how a single neuron responds to multiple synaptic inputs effectively and reliably. In primary visual cortex, repeated stimuli to one eye elicit neuronal responses of inherent variability and reliability. However, it remains unclear how this monocular variability and reliability contribute to the establishment of effective and reliable binocular responses and what drives this development. In this study, using in vivo multichannel extracellular recordings, we demonstrate binocular responses in adult mouse visual cortex exhibit low variability and high reliability. This response characteristic is immature during the critical period of binocular vision development. In amblyopic mice, the maturation of binocular variability and reliability is disrupted, and this defect can be partially rescued by enhancing cortical plasticity via dark exposure. In conclusion, the development of cortical response variability and reliability depends on the normal binocular visual experience, which is further regulated by cortical plasticity.